Widow Spider Parasitoids Philolema latrodecti (Fullaway) (Insecta: Hymenoptera: Eurytomidae) and Baeus latrodecti Dozier (Insecta: Hymenoptera: Platygastridae) - Christopher S. Bibbs; Lyle J. Buss (EDIS)
There are limited records of pathogens, parasites, and parasitoids known to affect widow spiders. This 4-page fact sheet describes what is known about two parasitoids, and observations from rearing them in the lab. Written by Christopher S. Bibbs and Lyle J. Buss, and published by the UF Department of Entomology and Nematology, January 2012.